Pengaruh Pembelajaran Daring Terhadap Indeks Prestasi Mahasiswa Pendidikan Kimia UIN Ar-RaniryAngkatan 2019 Selama Covid-19 - Salsabila, Sita Raihan; Muziatun, Hanum; Zulyani, Riza (Intelektualita: Journal of Education Sciences and Teacher Training, 2024)
This research is a descriptive and qualitative research that aims to know online learning effect which affects the grade point of UIN Ar-Raniry 2019 Chemistry Education’s colleger during this Covid-19 pandemic. This research has 40 respondents from a total of 65 UIN Ar-Raniry 2019 Chemistry Education’s colleger. Data analysis in this research is done by using  Miles and Huberman methode wchich includes 3 steps: data reduction,  presenting data, and taking conclusion and verification. Research’s result says that: online learning affects to great colleger’s grade point which is proved by grade point enhancement of 72,5% colleger of UIN Ar-Raniry 2019 Chemistry Education. That good influence is got because of the maximum effort of UIN Ar-Raniry Education Chemistries lecturers in online learnig using online media, well media choosen by lecterers, high enthusiasm and spirit of collegers in learning, and also well care and consideration of lecturer when collegers are in online learning’s obtacles. From that, online learning gives much effect to UIN Ar-Raniry 2019 Chemistry Education collegers during this Covid-19 pandemic that proved by enhancement of colleger’s grade point.